Young children spontaneously devise an optimal external solution to a cognitive problem. Issue 3 (9th December 2021) - Armitage, Kristy L.; Taylor, Alex H.; Suddendorf, Thomas; Redshaw, Jonathan
Abstract: Metacognition plays an essential role in adults' cognitive offloading decisions. Despite possessing basic metacognitive capacities, however, preschool‐aged children often fail to offload effectively. Here, we introduced 3‐ to 5‐year‐olds to a novel search task in which they were unlikely to perform optimally across trials without setting external reminders about the location of a target. Children watched as an experimenter first hid a target in one of three identical opaque containers. The containers were then shuffled out of view before children had to guess where the target was hidden. In the test phase, children could perform perfectly by simply placing a marker in a transparent jar attached to the target container prior to shuffling, and then later selecting the marked container. Children of all ages used this external strategy above chance levels if they had seen it demonstrated to them, but only the 4‐ and 5‐year‐olds independently devised the strategy to improve their future performance. These results suggest that, when necessary for optimal performance, even 4‐ and 5‐year‐olds can use metacognitive knowledge about their own future uncertainty to deploy effective external solutions.